ENT 530 Case Study: Kebab Kamil / Muhammad Haziq Ahmad Nazri ... [et al.] - Ahmad Nazri, Muhammad Haziq; Razali, Muhammad Izzam; Ghazali, Ahmad Adib; Mohd Shafuan, Nurul Faizah; Sabarudin, Nur Suriya; Mohd Fauzi, Siti Najiha; Hassan A Gani, Samsiah; Abdul Latiff, Siti Syaradibah (2021)
Kebab Kamil is a business that offers product and services to the customer who likes to eat Turkey shawarma that delicious and crunchy. Limited liability partnership is their form of business that the partners will be sharing the profit and loss of the business according of their ratios. Each of them will manage different task and have different responsibilities towards the business. Kebab Kamil was establish since 2020 until now. The strategic location to start their business of the Kebab Kamil is at Traffic light Kg Simpang Tok Ku, Kuala Terengganu, Terengganu. Based on our observation, the products of Kebab Kamil consist chicken and meat kebab that Turkey traditional foods that most of Malaysian will try and like it. It different from other food. The price of the Kebab Kamil also affordable for the customer, not that expensive kebab that sell at the restaurant. The case study will include company information, marketing strategy, operational strategy, company analysis which are strength, weakness, opportunities and threats. The most important is the financial achievement of this business.